Cervical Cancer Screening Using Pap Smear Test and Clinical Correlation (Medical Forum Monthly, 2022)
Objective: To screen for cervical cancer with the help of pap smear test and to analyze its clinical correlation.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Pak International Medical College, Peshawar from Jan 2019 to Jan 2020.Materials and Methods: The study was carried out on 40 sexually active women for over 4 months. All females were of >25 years. Pap smear was taken in lithotomy position. The sample was drawn from ectocervix by using wooden Ayre spatula rotated to about 360 degrees. It was then taken to lab for results. The lesions were categorized into negative intraepithelial neoplasm as well as epithelial cell abnormalities (ECA) in which both squamous and glandular cells were present. Treatment was given in accordance with the disease stage. The data that was collected was transformed into variables on IBM SPSS statistics 26.Results: In this study, 40 women were taken out of which 15 women revealed negative results while 25 showed signs of inflammation as well as infection. 20 women were asymptomatic, 7 revealed white vaginal discharge and 6 women were having irregular cycle. These were the most common symptoms. Others showed contact bleeding (n= 2), urinary incontinence (n=1) or excessive vaginal discharge (n= 4). The age of participants ranges from 26 to 65 years of age with mean age 37.07 years. Most of the women were falling in the age group of 30 to 50 years. Women having inflammation were starting from lower age group from 28 to 46 years.Conclusion: Cervical cancer can be avoided if adequate screening methods are used. The most frequent procedure for earlier detection and confirmation of cervical cancer is testing through Pap-smear A Pap smear is a quick, non-invasive, low-cost procedure. In a gynecologic setting, it is simple to diagnose precancerous lesions in women.